Scanning electron microscope study of fine and coarse airborne particle in Kuala Lumpur - Mohd. Yusoff, Mohd. Rashid; Mohd. Harun, Mohd. Harun (1988)
The 24-hr average concentration of fine (acrodynamic meter, da â‰¤ 2.5 um) and coarse (2.5 < da 10 um ) airborne particles collected at the UTM Air Quality Monitoring Station were studied under the scanning electron microscope (SEM). The microphotographs of both fine and coarse particles showed that the particles have various shapes. The agglomeration of these particles on the filter surface (due tp prolog sampling duration) make it difficult to resolve the particles individually. However, through approximation solutions, the fine sample was found to have higher particle count for a given area as compared to the coarse sample. Methods of improving the SEM techniques are also discussed.